[tex]f(x)=\frac{-2}{|x+3|}+4\\\\|x+3| \neq 0\\x+3 \neq 0 /-3\\x \neq -3\\\\-(x+3) \neq 0\\-x-3 \neq 0 /+3\\-x \neq 3 /*(-1)\\x \neq -3\\\\D: x \in R /\{-3\}\\D: x\in(-\infty; -3)U(-3; \infty)[/tex]
[tex]\frac{-2}{|x+3|}+4=0 /-4\\\frac{-2}{|x+3|}=-4 /*|x+3|\\-2=-4|x+3| /:(-4)\\\frac12=|x+3|\\\\x+3=\frac12 /-3\\x=-2.5\\\\-(x+3)=\frac12\\-x-3=\frac12 /+3\\-x=3.5\\x=-3.5[/tex]
[tex]\text{Miejsca zerowe: } x_1=-2.5; x_2=-3.5[/tex]
[tex]f(7)=\frac{-2}{|7+3|}+4=\frac{-2}{10}+4=-\frac15+4=3.8[/tex]
[tex]\frac{-2}{|x+3|}+4=2 /-4\\\frac{-2}{|x+3|}=-2 /*|x+3|\\-2=-2|x+3|\\-2(x+3)=-2\\-2x-6=-2 /+6\\-2x=4 /:(-2)\\x=-2\\\\-2(-(x+3))=-2\\-2(-x-3)=-2\\2x+6=-2 /-6\\2x=-8 /:2\\x=-4[/tex]
[tex]\text{Funkcja f przyjmuje wartosc 2 dla argumentow } x = -2, x=-4[/tex]